Approaching bibliometrics and prosopography: The comprehensive publishing landscape of CNPq (Brazil) and CONICET (Argentina) and its coverage in global databases - Digiampietri, Luciano (2024)
Global databases such as Web of Science and Scopus have determined the standard indicators to measure the research output in national comparisons and its quality evaluation for decades. Already classic studies of science proved that this landscape of scientific production was distorted by using overly selective bibliographical indexes that were considered “international databases” while their coverage was severely limited. A relevant part of the bibliometric literature in the last 10 years has revolved around the limitations of these global data sources and the search for alternatives to explore more comprehensive universes of the scholarly output, considering all disciplines and languages. Particularly relevant in this debate are some recently created bibliographic services and search engines that provide new opportunities: Dimensions, Lens, Open Alex, CrossRef and Google Scholar. Our specific contribution to these studies relies on a methodological shift based on a convergence between prosopography and bibliometrics. For that end, we selected two countries that can be considered “peripheral centers” in the Latin American region. Firstly, we determined a universe of national researchers of the National Council for Scientific and Technological Development (CNPq, Brazil) and the National Council for Scientific and Technical Research (CONICET, Argentina). The target populations are composed of 10,619 tenured researchers at CONICET and 14,418 holders of the CNPq’s “research productivity fellowship”. Secondly, we built a database with their comprehensive publishing performance uploaded in the national curricular information systems, the Brazilian Lattes and Argentina’s SIGEVA, that includes metadata for all articles. After computational and manual data cleaning of this database, we retained a total 464,361 articles for Brazil and 81,005 for Argentina published in 2013-2020. The comparative study shows that Argentina and Brazil have similar patterns of coverage in the global databases, although they differ in terms of collaboration practices and national publishing.